Exploration of an "Internet+" Grounded Approach for Establishing a Model for Evaluating Financial Management Risks in Enterprises - Wang, Hongli; Budsaratragoon, Pornanong (International Journal for Applied Information Management, 2023)
With the rapid development and continuous updating of computing technology, computer software is increasingly used in various management of enterprises, which brings great aspects to enterprise management and also creates high benefits for enterprises. This article takes the hospital as an example, based on Internet technology, evaluates the risks of the hospital financial management system, and establishes the relevant risk evaluation model according to the relevant elements of the medical financial management system. In the normal use of the hospital financial management ERP business, the risk consequences are formed through probability calculations. The evaluation value, and finally the evaluation value of the risk of the ERP project of the hospital financial management is calculated. The experimental results show that the average error between the evaluation results of the model and the actual financial value is only 2.429%, indicating that this evaluation method is highly accurate and has strong applicability.